Analisis Kepuasan Wisatawan Pada Daerah Kota Binjai Menggunakan Algoritma C4.5 Berbasis Mobile - Yelansya Ela; Eko Hariyanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Rating is a way or method to obtain information in any form that can be used as a basis for decision making. Ratings of a tourist object is often a standard for tourists to determine tourist destinations. Ratings made by tourists indicate the level of satisfaction with the services provided by each tourist attraction that has been visited. This study aims to determine and analyze the level of tourist satisfaction, especially in the city of Binjai using the C4.5 algorithm. Algorithm C4.5 is a technique in data mining to classify data with the concept of a decision tree. The data used to analyze the level of tourist satisfaction is data collected from respondents using an application built on the Android platform. Respondents who collected as many as 30 people were tourists who visited the Binjai City tourist attraction. The results of this study indicate that tourists are satisfied with the Cleanliness indicator which is indicated by the highest gain value of 0.283. While the lowest indicator is obtained in the parking variable with a gain value of 0.085. Based on the results of this research, it is hoped that it can become a reference for evaluating the services provided to increase tourist satisfaction